2022
DOI: 10.1016/j.annonc.2021.12.002
|View full text |Cite
|
Sign up to set email alerts
|

The ECHELON-2 Trial: 5-year results of a randomized, phase III study of brentuximab vedotin with chemotherapy for CD30-positive peripheral T-cell lymphoma

Abstract: The ECHELON-2 Trial: 5-year results of a randomized, phase 3 study of brentuximab vedotin with chemotherapy for CD30-positive peripheral T-cell lymphoma * , Annals of Oncology (2022), doi: https://doi.org/10.1016/j.annonc.2021.12.002. This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
113
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(117 citation statements)
references
References 38 publications
(67 reference statements)
1
113
0
3
Order By: Relevance
“…The recent identification and development of brentuximab vedotin (BV), an antibody–drug conjugate (ADC) consisting of a monoclonal antibody targeting CD30 coupled to the microtubule inhibitor monomethyl auristatin E (MMAE), represents a major milestone in the treatment of PTCL. The results of the ECHELON-2 study demonstrated that BV combined with CHP could provide clinically meaningful improvement as a first-line treatment for PTCL, achieving a 5-years PFS rate of 51.4% and a 5-years OS rate of 70.1% ( Horwitz et al, 2022 ).…”
Section: Current Status Of Peripheral T-cell Lymphoma Treatmentmentioning
confidence: 99%
“…The recent identification and development of brentuximab vedotin (BV), an antibody–drug conjugate (ADC) consisting of a monoclonal antibody targeting CD30 coupled to the microtubule inhibitor monomethyl auristatin E (MMAE), represents a major milestone in the treatment of PTCL. The results of the ECHELON-2 study demonstrated that BV combined with CHP could provide clinically meaningful improvement as a first-line treatment for PTCL, achieving a 5-years PFS rate of 51.4% and a 5-years OS rate of 70.1% ( Horwitz et al, 2022 ).…”
Section: Current Status Of Peripheral T-cell Lymphoma Treatmentmentioning
confidence: 99%
“…From the 5-year updated intention to treat analyses, frontline treatment with BV + CHP yielded superior outcomes as compared to CHOP. At the median follow-up of 47.6 months, 5-year PFS was 51.4% with BV + CHP vs. 43.0% with CHOP, and 5-year overall survival (OS) rates were 70.1% with BV + CHP vs 61.0% with CHOP [25]. Comparable efficacy was also observed among patients who relapsed and subsequently received BV monotherapy, with an ORR of 59% in patients retreated following BV + CHP as compared to 50% following CHOP.…”
Section: Brentuximab Vedotinmentioning
confidence: 99%
“…Comparable efficacy was also observed among patients who relapsed and subsequently received BV monotherapy, with an ORR of 59% in patients retreated following BV + CHP as compared to 50% following CHOP. Although ECHELON-2 was not powered to directly compare BV + CHP vs. CHOP among non-ALCL subgroups, responses trending towards superiority were observed in the major PTCL subtypes (despite wide confidence intervals) and were statistically significant in both ALK-positive and ALK-negative ALCL [25]. Adverse events (AEs) were generally similar between treatment arms, with peripheral sensory neuropathy reported in 52% of patients receiving BV + CHP and 55% of patients receiving CHOP.…”
Section: Brentuximab Vedotinmentioning
confidence: 99%
“…Given evidence of multidrug resistance by expression in relapsed and refractory lymphoma, prolonged exposure to doxorubicin and vincristine over a 4-day infusion may overcome resistance mechanism compared to the 1-day infusion used in CHOP [53] . In the phase II study of dose-adjusted Infusional etoposide, doxorubicin, and vincristine with cyclophosphamide and prednisone (EPOCH), 41 previously untreated patients with PTCL (excluding ATLL) were treated, leading to an ORR of 78% (with 61% achieving a complete response [CR]).…”
Section: Infusional Etoposide Doxorubicin and Vincristine With Cyclop...mentioning
confidence: 99%